PENINGKATAN SELF EFFICACY MAHASISWA JURUSAN TEKNIK SIPIL DENGAN PENGGUNAAN MODUL BERBASIS INKUIRI - Firmanilah Kamil (Fitrah, 2022)
Learning in higher education is focused on practical learning. Every practicum that is carried out requires basic knowledge, cooperation, and belief that comes from each individual. This belief is called self-efficacy. This study aims to determine the increase in student self-efficacy after carrying out learning with an inquiry-based module in the Soil Mechanics course. The self-efficacy measurement tool uses a questionnaire sheet containing 15 questions. The results showed an increase in self-efficacy in the experimental class and control class with a g value of 0.67 and 0.34 in the medium category.